The Visual Syntax of a Postcolony: Photographs in Zambia, 1930s – 1980s - Moronell, Sebastian Alfredo (Department of Historical Studies, 2023)
This dissertation investigates how photographs and photographic practices have both shaped and have been shaped by the political, cultural and performative demands of the project of postcolonial nation building in Zambia. Drawing on both visual and textual materials from the 1930s to the 1980s, collected from the National Archives of Zambia as well as several private collections, including that of the Fine Art Studios in Lusaka, this dissertation attempts to understand the different ways in which critical attention to the role of the mechanically reproduced images can allow us to reconsider the given boundaries between the colonial and the postcolonial, the public and the private, and the nation and the individual. The first chapter explores the methodological possibilities and the archival limits of writing a social history of photography in Zambia that still remains largely undocumented. The second chapter sifts through thousands of images haphazardly stored in the National Archives of Zambia, reflecting on the shift from the ethnographic mode of observation in the late colonial period to the concerted imaging of developmentalist spectacles in the early postcolonial period. The focus of the third chapter is on the politics of official images of Kenneth Kaunda, the first president of independent Zambia. This dissertation combines uses of photographs, archival documents, semi-structured interviews and brief auto-ethnographic observations.